Ekspresif Sarkasme dalam Akun Parodi di Instagram - Gina Aulia (Universitas Sebelas Maret, 2025)
Parody serves as a form of self-expression; therefore, the language employed tends to be humorous and sometimes illogical. However, the language used in parody also plays an essential role in ensuring that the intended message is effectively conveyed. The parodies featured on the Instagram account @parodi_barbie contain numerous instances of sarcastic expressions. The forms of sarcasm identified in these parodies vary, including illocutionary sarcasm, lexical sarcasm, like-prefixed sarcasm, and propositional sarcasm. The purpose of this study is to analyze the types of sarcasm found in the parodies and to explain the communicative functions of sarcasm presented in the Instagram account @parodi_barbie. This research employs a descriptive qualitative method. The research objects are parody videos from the @parodi_barbie Instagram account, with a total of ten videos selected as data sources. The selected videos are those with the highest number of viewers on the account. The findings reveal a total of 26 instances of sarcasm. Among these, propositional sarcasm appears most frequently (42%), followed by illocutionary sarcasm (27%), lexical sarcasm (23%), and like-prefixed sarcasm (8%). Based on the data analysis, it can be concluded that the parodies on this account often address various social issues occurring in society. However, the criticism is delivered humorously, allowing it to be received positively by the audience.